KAPASITAS PEMERINTAH PROVINSI JAMBI DALAM MENGHADAPI BENCANA BANJIR DAN ASAP AKIBAT KEBAKARAN HUTAN DAN LAHAN - Intan Adhi Perdana Putri (Research Centre for Population, Indonesian Institute of Sciences, 2019)
Preventing and reducing disaster victims is crucial in the disaster risk reduction context. The government, particularly at the local level, plays a vital role in reducing such risk. Therefore, strengthening the capacity of local governments is needed to reach the goal. This necessity is clearly stated in the Sendai Framework for Disaster Risk Reduction (SFDDR) 2015-2030. The capacity of local government in disaster risk management is essential in preventing and minimizing the number of victims. Floods and forest and land fire haze are the most common disasters in Jambi Province. Understanding the local government capacity is imperative in the context of disaster risk reduction as such. This paper aims to explain the current capacity of the Jambi local government in managing flood and forest and land fire haze. Data were collected qualitatively from government officials through focus group discussions (FGDs) and interviews. The findings showed that the capacity of Jambiâ€™s local government needs to be improved, and there are issues to be solved. Jambi Province policy capacity tended to focus on forest fires and lacked attention on flood-related policies. On implementation capacity, there exist some issues to be overcome, such as the local government officialsâ€™ knowledge and skills related to disaster risk management, redundant disaster preparedness programs at the village level, and the need for more detailed hazard maps.Â